Ex Ante Price Offers in Matching Games Non-Steady States - Peters, Michael (Econometrica, 1991)
A matching problem is considered in which sellers can publicly commit to a trading price that differs from the price at which buyers expect to trade elsewhere in the market. When demand and supply are nearly equal, the equilibrium ex ante price offer lies below the price associated with the Nash bargaining split. This relationship reverses when the level of excess demand is large. Sellers always have an incentive to make ex ante offers when prices elsewhere are determined by Nash bargaining. This can be interpreted to mean that Nash bargaining is an unstable pricing institution. Copyright 1991 by The Econometric Society.